The effect of magnesium supplementation on serum concentration of lipid profile: an updated systematic review and dose-response meta-analysis on randomized controlled trials - Mitra Hariri; Masoudreza Sohrabi; Ali Gholami (Nutrition Journal)
Abstract Background Some evidence suggests magnesium might reduce serum levels of lipid profile. Due to the significance of this matter on hand, we centralized our aim to conduct a systematic review and meta-analysis to interrogate the effect of magnesium supplementation on serum levels of total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C), and high density lipoprotein cholesterol (HDL-C) in the general population aged ≥ 18 years. Methods In line with conducting this study first, relevant articles were found through searching databases, including five databases: Cochrane Library, ClinicalTrials.gov, ISI Web of Science, Scopus, and PubMed until January 2024. Following fulfilling the first aim, their mean differences and standard deviations were calculated to conduct the meta-analysis. Ultimately, an assessment of the statistical heterogeneity of intervention effects was performed using I-squared statistics and Cochran’s Q test. Results Regarding serum levels of TC, TG, LDL-C, and HDL-C, twenty-one, twenty-three, twenty, and twenty-five studies were included in the meta-analysis. The pooled estimates showed no significant differences in serum levels of TC, TG, and LDL-C between the magnesium group and comparison group (weighted mean difference (WMD) = 0.34 mg/dl, 95% confidence interval (CI): -1.75 to 2.43, P = 0.749, I 2  = 99.1%; WMD=-2.06 mg/dl, 95% CI: -6.35 to 2.23, P = 0.346, I 2  = 99.1; WMD = 1.71 mg/dl, 95% CI: -0.81 to 4.24, P = 0.183, I 2  = 99.4, respectively). However, magnesium significantly increased HDL-C (WMD = 1.21 mg/dl, 95% CI: 0.58 to 1.85, P < 0.001, I 2  = 99.5). Conclusion In conclusion, our study showed that magnesium significantly increased HDL-C levels. However, due to high heterogeneity, we must note that more research is needed to make robust recommendations regarding magnesium supplementation in clinical practice. Registry number This study was registered in PROSPERO under the protocol number CRD42024505142.